Mechanical Properties and Accuracy Evaluation of 3D Printing Based on Value in the Munsell Color System - Jianping Huang; Wanxiang Ye; Guihua Ye; Qi Jia; Kelun Li; Jiawen Kong; Heng Bo Jiang; Qing Lan; Liming Yu (Advances in Materials Science and Engineering)
Aim. Printing parameters have been studied extensively to improve printing performance, while resins have been studied to a lesser extent. Therefore, we explore the impact of value in the Munsell color system on the mechanical properties and accuracy of printed products. Materials and Methods. Resins having different values were prepared by mixing transparent resin and color pastes. We used plate models for mechanical measurement, crown-and bridge models for accuracy measurement, and disc models for color measurement. Results. The Group E resin, which had the lowest value, had the minimum ultimate flexural strength (61.199 MPa) and a relatively low elastic modulus (19.015 MPa). Excluding the d index, no significant difference in accuracy was observed. In terms of the d index of trueness, the result of the Group E resin was significantly low. The relative errors of trueness were less than 0.0727 μm. The relative errors of precision were less than 0.0093 μm. Conclusion. The value of a resin affects the mechanical properties and accuracy of printed products. It is better to secure flexural strength by using a lower-value resin. High-value resins have relatively low accuracies.